In situ observations of liquid-liquid phase separation in aqueous ZnSO4 solutions at temperatures up to 400 °C: Implications for Zn2+-SO4 2- association and evolution of submarine hydrothermal fluids - Wang, X.; Wan, Y.; Hu, W.; Chou, I.; Cao, J.; Wang, X.; Wang, M.; Li, Zhen (Pergamon, 2016)
Liquid-liquid immiscibility is gaining recognition as an important process in hydrothermal fluid activity. However, studies of this complex process are relatively limited. We examined liquid-liquid immiscibility in aqueous ZnSO4 solutions at temperatures above ~266.5 °C and at vapor-saturation pressures. The homogeneous aqueous ZnSO4 solution separated into ZnSO4-rich (L1) and ZnSO4-poor (L2) liquid phases coexisting with the vapor phase. The L1-L2 phase separation temperature decreased with increasing ZnSO4 concentration up to 1.0 mol/kg, and then increased at greater ZnSO4 concentrations, showing a typical lower critical solution temperature (LCST) of ~266.5 °C. Gunningite (ZnSO4·H2O) precipitated in 2.0 mol/kg ZnSO4 solution at 360 °C. The L1-L2 phase separation resulted mainly from the strong Zn2+-SO4 2- association at high temperatures. The major results of this study are: (1) the discovery of the LCST in these systems, a macroscale property associated with polymeric mixtures; (2) analyses of the peak area ratios of the v1(SO4 2-) and OH stretching bands, which suggest that the sulfate concentration increases with increasing temperature in L1, especially above 375 °C; (3) a new Raman v1(SO4 2-) mode at ~1005 cm-1 observed only in the L1 phase, whose fraction increases with increasing temperature; and (4) the shape of the OH Raman stretching band, which indicates that water molecules and solute interact much more strongly in L1 than in the coexisting L2 phase, suggesting that water molecules fit into the framework formed by various Zn2+-SO4 2- pairs and chain structures in L1.These results have potential implications for understanding transport and reduction of seawater-derived sulfate in submarine hydrothermal systems. The formation of an immiscible sulfate-rich liquid phase can favor the circulation of sulfate within mid-ocean ridge basalt because the sulfate-rich liquid density is higher than that of the coexisting fluid. The reduction of sulfate could also be accelerated because sulfate is locally concentrated and strong Zn2+-SO4 2- association increases the reactivity of sulfate.